2017
DOI: 10.1002/slct.201700572
|View full text |Cite
|
Sign up to set email alerts
|

Cycling Fading Mechanism for a Bismuth Fluoride Electrode in a Lithium‐Ion Battery

Abstract: The nanocomposite of BiF3 and carbon (BiF3/C) is a promising cathode material for lithium‐ion batteries because of its high capacity. When BiF3/C was charged and discharged within voltage range of 2.0–4.5 V, the BiF3/C exhibited high capacity; however, as the cycle progressed, the discharge‐charge capacities decreased and the charge voltage shifted towards higher region. When charge cut‐off voltage was changed from 4.5 to 3.5 V, the capacity degradation was suppressed. This indicates that the cause of capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
0
13
0
2
Order By: Relevance
“…The SEI layer may decompose during the following charge to oxygen‐rich products that destabilize the electrode material. Furthermore, the repeated formation and decomposition of the SEI layer not only depletes the electrolyte but also retards the conversion reaction from Bi and LiF into BiF 3 . Consequently, both BiF 3 and BiF 3 /C electrode materials show severe capacity decay during cycling.…”
Section: Halides In Lithium‐ion Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The SEI layer may decompose during the following charge to oxygen‐rich products that destabilize the electrode material. Furthermore, the repeated formation and decomposition of the SEI layer not only depletes the electrolyte but also retards the conversion reaction from Bi and LiF into BiF 3 . Consequently, both BiF 3 and BiF 3 /C electrode materials show severe capacity decay during cycling.…”
Section: Halides In Lithium‐ion Batteriesmentioning
confidence: 99%
“…Furthermore,t he repeated formation and decomposition of the SEI layer not only depletes the electrolyte but also retards the conversion reaction from Bi and LiF into BiF 3 . [108] Consequently,b oth BiF 3 and BiF 3 /C electrode materials show severe capacity decay during cycling.A matucci and co-workers found that the acyclic organic carbonate solvents showed good compatibility with the Bi metal. [106,107] TheBiF 3 electrode exhibited am uch better cycling stability in 1m LiPF 6 /ethyl methyl carbonate (EMC) than in ethylene carbonate (EC)/dimethyl carbonate (DMC).…”
Section: Halide-based Electrode Materialsmentioning
confidence: 99%
“…Die SEI‐Schicht könnte sich während der nächsten Ladung zu sauerstoffreichen Produkten, die das Elektrodenmaterial destabilisieren, zersetzen. Des Weiteren baut die wiederholte Bildung und Zersetzung der SEI‐Schicht nicht nur den Elektrolyten ab, sondern verzögert auch die Konversionsreaktion von Bi und Li zu BiF 3 . Als Konsequenz daraus zeigen sowohl BiF 3 als auch BiF 3 /C‐Elektrodenmaterialien starken Kapazitätsabbau während der Zyklierung.…”
Section: Halogenide In Lithium‐ionen‐batterienunclassified
“…Schicht nicht nur den Elektrolyten ab,s ondern verzçgert auch die Konversionsreaktion von Bi und Li zu BiF 3 [108]. Als Konsequenz daraus zeigen sowohl BiF 3 als auch BiF 3 /C-Elektrodenmaterialien starken Kapazitätsabbau während der Zyklierung.A matucci et al stellten fest, dass acyclische organische Carbonat-Lçsungsmittel gute Kompatibilitätm it dem Bi-Metall aufweisen [106,107].…”
unclassified
“…For instance, bismuth fluoride (BiF3) is a particularly attractive owing to its high theoretical specific capacity (302 mAh g 1 ); however, the high reactivity of Bi (discharged state) with electrolytes [26,27] and the low electronic conductivity of BiF3…”
Section: Introductionmentioning
confidence: 99%